Stable Isotopic Evidence for Human and Animal Diets From the Late Neolithic to the Ming Dynasty in the Middle-Lower Reaches of the Hulu River Valley, NW China - Dong, Jiajia; Wang, Shan; Chen, Guoke; Wei, Wenyu; Du, Linyao; Xu, Yongxiang; Ma, Minmin; Dong, Guanghui (Frontiers in Ecology and Evolution, 2022)
The study of human and animal paleodiets, representing the unique subsistence strategies and human-environment interactions adopted over evolutionary time, has attracted intensive research attention. Historically, the western Loess Plateau (WLP) served as a key area for the evolution of human-land relationship. The human subsistence patterns in the WLP changed significantly from prehistoric to historical periods based on archaeobotanical data. However, the trajectory and influencing factors of ancient human and animal diets in the WLP remain unclear, mainly due to the lack of isotopic data in the upper reaches of the Wei River. In this paper, we reported 172 human and animal isotope samples (C and N) and 23 radiocarbon dates from three sites in the middle-lower reaches of the Hulu River Valley (HRV). At least three periods of dietary patterns for humans were observed in the WLP from the late Neolithic to Ming Dynasty. During 5300-4000 Before Present (BP), humans and domesticated animals such as pigs and dogs consumed a greater proportion of millets and millet byproducts. Between 3000 and 2200 BP, the diets of pigs and dogs remained largely comprised of C4 foods, while humans consumed both C3 and C4 foods, which contradicted the evidence of an overwhelming proportion of wheat and barley (C3 crops) from the contemporaneous cultural sediment. The contradictions between plant remains and human diets are probably related to geopolitical factors. Between 1000-500 BP, human diets were more diverse and heterogeneous in this region. Combined with environmental and archaeological evidence, the changes in diets and subsistence strategies over the three periods can be attributed to the comprehensive influence of regional cultural development, geopolitics and technological innovation. This paper not only reveals the trajectory and influencing factors of ancient human and animal diets in the middle-lower HRV, but also explores how subsistence strategies, particularly in terms of dietary structure, will change in the context of cultural exchange and diffusion, and emphasizes the important influence of geopolitical interactions in the WLP.